Integrating Banking Fundamental Factors with Financial Technology in Reducing Banking Risk - Adrianna Syariefur Rakhmat; Mohammad Hatta Fahamsyah; Preatmi Nurastuti; Muhammad Hamdan Ainulyaqin (PT FORMOSA CENDEKIA GLOBAL, 2023)
Fintech has been successful in producing new models in financial services, and creating solutions. Fintech is able to improve risk handling capabilities and reduce the possibility of risks. This research is a quantitative research that measures how Fintech can moderate banking fundamental factors in reducing banking risk. This study uses secondary data sourced from the Financial Services Authority and Bank Indonesia from April 2020 to April 2023. This research used Ordinary Least Square (OLS) to determine the magnitude and significance effect of fintech on non performing loan rate. The result showed that Fintech can reduce banking risk and Loan to Deposit Ratio (LDR) can increase banking risk.